PENGARUH STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PERUSAHAAN : STUDI KASUS PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERCATAT DI BURSA EFEK INDONESIA, 2005-2011 - Fadilah, Ansoriyah (Jurnal Kajian Ekonomi dan Keuangan, 2012)
The purpose of this study was to analyze the impact of capital structure on financial performance of mining sector companies listed in the Indonesia Stock Exchange (BEI). This study employed the descriptive analysis and a regression analysis of panel data. This study covered annual data of 30 mining sector companies listed in the BEI in a 7-year time horizon (20052011). The descriptive analysis showed that most of companies applied a low-leverage policy in their capital structure. In average, the companies generate a good financial performance, in terms of profitability ratios and market based ratios. The regression analysis of panel data showed that capital structure has a significant impact on the company's fnancial performance based on ROA, ROE, and PER, but have insignificant effect on the company's financial performance based on market-to-book value ratio.